FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI KABUPATEN KEPULAUAN TALAUD - Latjandu, Imelda; Kalangi, Lintje; Tinangon, Jantje J. (ACCOUNTABILITY, 2016)
This research aims to analyze the influence of organization commitment, human resources competence, utilization of information technology, and the effectiveness of internal control to quality of government financial statement at Talaud Island Regency Government. The sample in this research were the Head and Accounting Staff at Talaud Island Regency Government as 64 respondents. This research is quantitative using multiple regression analysis. To test the data quality by validity and reliability. Beside that testing by the classical assumption of normality, multicollinearity and heteroscedasticity. This research result indicates that organization commitment, utilization of information technology, and the effectiveness of internal control has effect significantly to the quality of government financial statements at Talaud island Regency Government and the human resource competence has effect but not significantly to quality of government financial statement at Talaud Island Regency Government. Suggestions to Talaud Island Regency Government is expected to improve qualifications in the field of education, namely the employees who receive educational background in accounting, as seen from the respondent data, proving that there are many officers who worked in the accounting who have educational non accounting. Keywords: Quality of Local Government Financial Statements, Organization Commitment, Human Resources Competence, Utilization of Information Technology, and the Effectiveness of Internal Control